The Histone Deacetylase Activator ITSA-1 Improves the Prognosis of Cardiac Arrest Rats by Alleviating Systemic Inflammatory Responses Following Cardiopulmonary Resuscitation - Chenyu Zhang; Hongyan Wei; Qiang Zhang; Haohong Zhan; Yuanzheng Lu; Yujie Li; Bo Li; Wen Huang; Feng Nian; Rong Liu; Chunlin Hu; Jie Chen (Mediators of Inflammation)
Conclusion: ITSA-1 enhances the recovery and survival of post-ROSC rats by diminishing histone acetylation and mitigating systemic inflammation. This effect is possibly due to the inhibition of glial cell activation, increased neuronal survival in the brain, and improved cardiac output (CO) and ejection fraction (EF).